2016
DOI: 10.12944/cwe.11.3.26
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Supply Chain of Pangasius in India: A Case of Andhra Pradesh

Abstract: The paper delineates the distribution, communication and price transmission along the supply chain. Pangasius was mainly produced and supplied from state of Andhra Pradesh to several states in India. The major share of Pangasius traded to West Bengal (73.29%) and Maharashtra (16.4%) and hence the study was restricted to these two states. The three marketing channels were identified (A, B and C) and the major volume was transacted through the channel (B). The stakeholders identified in marketing were farmers, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Of the 25 species traded across the different markets it was found that the among the identified species Catla, Rohu, Tilapia and Pangasius has the highest diversity of 1.0 which indicated that among the 7 markets selected Catla, Rohu, Tilapia and Pangasius are the most available and accessible and traded fish across the markets. Mugaonkar et al (12) examined the Delineation of Supply chain of Pangasius in India-A case of Andhra Pradesh. The study found that the Pangasius was mainly produced and supplied from state of Andhra Finfishes and crustaceans were the major groups contributing to the fishery of this region.…”
Section: Species and Market Diversity Analysismentioning
confidence: 99%
“…Of the 25 species traded across the different markets it was found that the among the identified species Catla, Rohu, Tilapia and Pangasius has the highest diversity of 1.0 which indicated that among the 7 markets selected Catla, Rohu, Tilapia and Pangasius are the most available and accessible and traded fish across the markets. Mugaonkar et al (12) examined the Delineation of Supply chain of Pangasius in India-A case of Andhra Pradesh. The study found that the Pangasius was mainly produced and supplied from state of Andhra Finfishes and crustaceans were the major groups contributing to the fishery of this region.…”
Section: Species and Market Diversity Analysismentioning
confidence: 99%
“…Huge supply of Pangasius fish has caused prices to crash by more than 50% and resulted in heavy losses to small farmers who exited from Pangasius farming subsequently (Belton et al, 2017) [9] . The market avenues for the Pangasius are scanty and limited (Mugaonkar et al, 2016) [29] when compared to the wellestablished trading network and consumer markets of the Indian major carps, As a result, farming of Pangasius (P. hypophthalmus) is now restricted to 14,000 ha (Fig. 2) covering approximately 7-8% of the total fish culture area in Krishna-Godavari Delta region with stabilized production of 250,000 tonnes (Fig.…”
mentioning
confidence: 99%